2022
DOI: 10.1101/2022.10.31.514466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

USP10 strikes down β-catenin by dual-wielding deubiquitinase activity and phase separation potential

Abstract: Wnt/β-catenin signaling is a conserved pathway crucially governing development, tissue homeostasis and oncogenesis in metazoan. Through screening, we identified a deubiquitinase (DUB) USP10 as a novel modulator of Wnt/β-catenin signaling. Mechanistically, USP10 binds to Axin1 via conserved motifs and stabilizes Axin1 through K48-linked deubiquitination. And in parallel, USP10 tethers Axin1 and β-catenin physically, via stabilizing the phase separation of Axin1 through its intrinsically-disordered regions, whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 64 publications
(166 reference statements)
1
12
0
Order By: Relevance
“…We found that the use of AMPK agonists significantly reduced of TOPFlash reporter intensity under Wnt3a conditioned medium only when USP10 was present (Fig. 1G) [17]. We mutated Ser76 on USP10 to mimic the presence (S76D) and absence (S76A) of AMPK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that the use of AMPK agonists significantly reduced of TOPFlash reporter intensity under Wnt3a conditioned medium only when USP10 was present (Fig. 1G) [17]. We mutated Ser76 on USP10 to mimic the presence (S76D) and absence (S76A) of AMPK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our recent report of the physical role of USP10 [17], we tested whether AMPK phosphorylation could alter the physical property of USP10. Interestingly, we found that USP10‐S76A showed minimal binding toward β‐catenin, and the phosphorylation‐mimic mutant, S76D, behaved oppositely (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations